ASYNCHRONOUS ONLINE DISCUSSION: ENHANCING STUDENT PARTICIPATION - Fenny Veranika (ICoTE Proceedings)
The existence and boom of internet use among the net Generation highlights the benefits of asynchronous online discussion (AOD) in higher educational context. The convenience to learn at anytime from anywhere as well as building collaborative learning has led many experts to suggest AOD as a promising tool in extending language teaching learning. Regrettably, in this era of internet and Computer Mediated Communication (CMC) popularity, the implementation of AOD in language teaching learning are still limited in number. Even, in this infancy stage, many educators simply apply AOD to bricks mortar classes without optimally structure, which results in lower student participation. In addition, most of the contributions by students were in surface level of knowledge construction and in serial monologues. To address these issues, this article offers a view on the need of integrating AOD in teaching learning language and an instructional strategy called Starter Wrapper technique to structure and manage online discussion for the purpose of generating more student participation.